Synthesis of new triazole derivatives and their potential applications for removal of heavy metals from aqueous solution and antibacterial activities - Xu, Chunyun; Yang, Na; Yu, Haichun; Wang, Xiaojing (Frontiers in Chemistry, 2024)
In this paper, triazole derivatives were prepared by a three-step mild reaction using carbon disulfide as starting material. In face of microbial threats, we found that compound 3-cyclopropyl-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazole-6-thiol (C2) has good antibacterial activity, inhibition and clearance ability against biofilms, low hemolytic activity and toxicity, good anti-inflammatory activity. At the same time, we found that B and C series compounds have good metal ion scavenging ability, with removal rates of C series ranging from 47% to 67% and B series ranging from 67% to 87%.